2022
DOI: 10.1038/s41467-022-33294-w
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage-antibiotic combination therapy against extensively drug-resistant Pseudomonas aeruginosa infection to allow liver transplantation in a toddler

Abstract: Post-operative bacterial infections are a leading cause of mortality and morbidity after ongoing liver transplantation. Bacteria causing these infections in the hospital setting can exhibit high degrees of resistance to multiple types of antibiotics, which leads to major therapeutic hurdles. Alternate ways of treating these antibiotic-resistant infections are thus urgently needed. Phage therapy is one of them and consists in using selected bacteriophage viruses – viruses who specifically prey on bacteria, natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…The combination of phages and antibiotics has been widely used to enhance the eradication of drug-resistant bacteria and mitigate the spread of antibiotic resistance worldwide (8, 46, 47). Several studies have examined the mechanisms underlying phage-antibiotic synergy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of phages and antibiotics has been widely used to enhance the eradication of drug-resistant bacteria and mitigate the spread of antibiotic resistance worldwide (8, 46, 47). Several studies have examined the mechanisms underlying phage-antibiotic synergy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the mechanisms underlying phage-antibiotic synergy. Owing to the selection pressure on bacteria caused by phage infection, some toxicity, drug sensitivity, and growth factors are lost, and phage-resistant strains are often less toxic, more sensitive to antibiotics, and grow at a slower rate than wild-type strains (46, 47). Combining phages with antibiotics can reduce resistant clones, as our study showed, but the type of phage utilized will affect the outcome (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, a combinatorial treatment of phages and antibiotics is likely even more effective (39). For example, bacteriophage cocktailantibiotic combination therapy against extensively drug-resistant P. aeruginosa infection allowed liver transplantation in a toddler with recalcitrant infection (40). The rationale is that the target for this phage may be selected against, and therefore multiple venues of attack make evolutionary escape less likely.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the major therapeutic hurdles of antibiotics and other chemotherapies caused by high degrees of bacteria resistance in clinic, phage therapy provides a new therapeutic approach for precisely editing the intestinal microbiota, completely resolving bacteria resistance and treating liver diseases. Although great advances have presented in various bacterial infection ( Mitropoulou et al., 2022 ; Van Nieuwenhuyse et al., 2022 ), due to the diversity and complexity of gut microbiome, more clinical trials with larger cohorts are required to validate the relevance of the findings in NAFLD patients.…”
Section: Novel Strategy For Nafld Treatment Based On Gut Microbiotamentioning
confidence: 99%